Evidence‐Based Medicine in Otolaryngology Part 4: Everyday Probabilities—Nonbinary Diagnostic Tests. Issue 2 (28th May 2013) - Shin, Jennifer J.; Stinnett, Sandra S.; Randolph, Gregory W.
Abstract : Many diagnostic tests have nonbinary results. Thus, this fourth installment of our series in evidence‐based medicine in otolaryngology focuses on understanding diagnostic tests with more than 2 possible results. We begin with a brief review of the types of multilevel results to be considered: continuous, ordinal, and nominal. Next, we discuss each of type in greater detail, including the methods to determine the posttest probability associated with each type of test result. The use of serial diagnostic tests and practicalities are also discussed. Frequently used diagnostic tests are utilized as examples.